1992
DOI: 10.1051/agro:19920703
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the variability of sugar beet (Beta vulgaris L) growth during the early stages. I. Influence of various conditions on crop establishment

Abstract: Summary — The expansion of the sugar beet leaf canopy tends to be slow in the north of France. This is an important source of loss of yield. This study identifies the main sources of growth variability before competition starts between plants. Field

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Figure 7 summarizes the factors that may give rise to the variability in seedling size. Once the true leaves are functioning, the RGR is fairly constant, whatever the seedling size (Boiffin et al, 1992 …”
Section: Observations and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 summarizes the factors that may give rise to the variability in seedling size. Once the true leaves are functioning, the RGR is fairly constant, whatever the seedling size (Boiffin et al, 1992 …”
Section: Observations and Measurementsmentioning
confidence: 99%
“…We have previously shown (Boiffin et al, 1992) that differences in individual biomass measured (1974) found that seed size strongly influenced plant growth. Such an influence has also been found for other cultivated species.…”
Section: Introductionmentioning
confidence: 96%
“…Sugar beet was chosen because it requires demanding seedbed conditions [6,18] as it must be established within a short lapse of time and because the duration of its growing cycle must be optimal [5,9]. In brief, for sugar beet seedbed preparation, the question of the possible days for tilling is crucial.…”
Section: Materials Methods and Resultsmentioning
confidence: 99%
“…Variables related to thermal time (GDD, growth degree-day) were calculated daily and on an accumulated basis, using a base temperature of 3 • C [26,49]. GDD was strongly related to phenological development and growth stage [50].…”
Section: Field Trialsmentioning
confidence: 99%